Effect of Moringa Leaves and Jackfruit Seeds as Rice Substitute to Reduce Blood Glucose Levels in Mice - I Gusti Ngurah Agung Adi Primantara; Komang Astri Mahadewi; I Gede Aditya Arimbawa; Marvel Alden Muljosaputro; Komang Dinda Bagus Putra Suryawan; Putu Nia Calista Santoso; Ni Luh Putu Eka Kartika Sari (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Most Indonesians consume white rice, which has a high Glycemic Index (GI). Eating foods with high GI can lead to the occurrence of Diabetes Mellitus (DM). DM is a metabolic disorder characterized by chronic hyperglycemia. Alternative solutions are needed to overcome diabetes mellitus, one of which is by using rice substitute which has a low Glycemic Index (GI). Moringa leaves (Moringa oleifera) and jackfruit seeds (Artocarpus heterophyllus lam.) contain flavonoids that have the potential to be used as ingredients for making rice substitute. Flavonoids function to increase antioxidant enzymes, neutralize free radicals, lower blood sugar, overcome fatigue, and protect insulin-producing pancreatic ß cells. This study aims to analyze the content, physical and chemical characteristics, and antidiabetic activity of innovative rice substitute. In this study, an rice substitute formulation was made from Moringa flour: jackfruit flour in the ratio of 3:1 (P1), 1:1 (P2), and 1:3 (P3). Analog rice was tested on mice which were divided into five groups, namely positive control, negative control, and a combination of extracts P1, P2, and P3. Data analysis was carried out using SPSS 25 software. The results obtained showed that the rice substitute formulations P1, P2, and P3 were able to reduce blood sugar in mice, but P2 best reduced blood sugar, which was 11 mg/dL and 22 mg/dL.